China’s Green Bond Market: Structural Characteristics, Formation Factors, and Development Suggestions—Based on the Comparison of the Chinese and the US Green Bond Markets Structure - Haolan Li; Tiancheng He; Xihong Liao; Weizhen Tong (International Journal of Antennas and Propagation)
Since 2012, green bond markets have boomed worldwide, particularly in the European Union, the United States, and China. Under this background, the researchers use the methods of literature research, qualitative analysis, and descriptive research to compare the structure of Chinese and American green bond markets and analyze their differences from the perspective of historical evolution, issuance standards, and market operation characteristics. The researchers believe that China’s bank-oriented financial structure and America’s market-oriented financial structure are the main reasons for the difference between the two countries. The researchers then discuss the strengths and weaknesses of China’s green bond market and conclude that the advantages of China’s green bond market structure lie in low risk and close relationships between banks and enterprises, while the disadvantages lie in low financial efficiency and give relevant suggestions. This article makes up for the lack of cross-country comparison in the existing research on the green bond market and provides a qualitative research perspective. The suggestions put forward have specific policy significance for developing the green bond market in China and other developing countries.